2014
DOI: 10.1590/1678-775720140117
|View full text |Cite
|
Sign up to set email alerts
|

Thickness and marking quality of different occlusal contact registration strips

Abstract: Objectives Evaluate the thickness and the marking quality of different occlusal contact registration strips (OCRS) and a possible correlation between them.Material and Methods The following OCRS were selected: Accufilm II, BK20, BK21, BK22, BK23, BK28, and BK31. The thickness was measured in three points of the OCRS with an electronic measuring device (TESA), and the mean was calculated. To produce the marks on the strips, composite resin specimens were adapted to a universal testing machine (Versat 2000) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Reproducibility of visual occlusal detection methods is unreliable even when identical occlusal marking mediums are used on identical occlusal contacts . Conflicting results have been published about the relationships between contact mark size and force magnitude and between mark size and product thickness . Another study demonstrated that thick products elicit a proprioceptive response, comparable to occluding on a cotton roll, which can alter the direction of the mandible on closing, while thinner products tend to allow the mandible and its musculature to act similarly to a natural bite .…”
Section: Introductionmentioning
confidence: 99%
“…Reproducibility of visual occlusal detection methods is unreliable even when identical occlusal marking mediums are used on identical occlusal contacts . Conflicting results have been published about the relationships between contact mark size and force magnitude and between mark size and product thickness . Another study demonstrated that thick products elicit a proprioceptive response, comparable to occluding on a cotton roll, which can alter the direction of the mandible on closing, while thinner products tend to allow the mandible and its musculature to act similarly to a natural bite .…”
Section: Introductionmentioning
confidence: 99%